أخلاقيات الخطاب في النقد العربي القديم - عبـدالقاهر الجرجـاني أنموذجاً - AlDukan | الدكان, Muhammad bin Saad | محمد بن سعد (2023)
This research deals with an important issue in the world of critical knowledge, which is the critical discourse in its ethical dimension. This critic has epistemological and methodological traits, which the researcher believes is worthy of research, accountability and reflection. , objectivity, and originality, and the second turns to the language ethics of Al-Jurjani in his critical discourse, that at the level of politeness, or at the level of sophistication, or, at the level of pilgrims, in an epistemological attempt by the researcher to return to the roots, and to reveal the complete sincerity of the critic Ethics in his speech, and its adoption as a ruling model in the critical cognitive process, in a contemporary world preoccupied with overlapping visions, with separation more than communication, and with the divergent preoccupations of each scientific field in its various fields. | يتناول هذا البحث قضية مهمة في عالم المعرفة النقدية, و هي الخطاب النقدي في بعده الأخلاقي, و قد احتار الباحث نموذجا من النقد العربي القديم , تمثل في عبد القاهر الجرجاني, لما له من مكانة مركزية على مستوى المعرفة البلاغية و النقدية, ولما يتسم به خطاب هذا الناقد من سمات معرفية و منهجية أخلاقية, يرى الباحث أنها تستحق البحث و المساءلة و التأمل, و قد جاء هذا البحث في مبحثين أول يتجه الى أخلاقيات المنهج النقدي عند الجرجاني , و في كنف هذا المبحث تأتي المقاربة لبعض القيم المنهجية من الناحية الأخلاقية : المسؤولية, و الموضوعية, و الاصالة, و ثان يتجه الى أخلاقيات اللغة عند الجرجاني في خطابه النقدي, ان على مستوى التأدب , أو على مستوى التفنن, أ, على مستوى الحجاج, في محاولة معرفية من الباحث للعودة الى الجذور, و الكشف عن اخلاص الناقد التام للأخلاق في خطابه, و اعتمادها نموذجا حاكما في العملية المعرفية النقدية, في عالم معاصر منشغل بالرؤى المتداخلة, بالانفصال أكثر من الاتصال, وبالانشغالات المتشعبة لكل حقل علمي في حقوله المتنوعة.